profesionalitas guru dalam pencapaian kompetensi belajar peserta didi pada mata pelajaran pendidikan agama islam dan budi pekerti di SM Negeri 1 TELAGA, Kabupaten Gorontalo: studi pasal 20 undang-undang republik indonesia nomor 14 tahun 2005 tentang guru dan dosen - inda sarii ismail (Pekerti: Journal Pendidikan Islam dan Budi Pekerti, 2025)
This article examines teacher professionalism in achieving student learning competencies in Islamic religious education and character subjects at SMP Negeri 1 Telaga, Gorontalo Regency. This research method uses a qualitative type of research with a case study approach. The results of the research show that teacher professionalism in the teaching and learning process at SMP Negeri 1 Telaga, Gorontalo district, in general, teachers have created a learning process in accordance with what has been planned by the school. However, researchers see that the implementation of learning has not been effective or carried out well, this is because teachers have not been able to carry out their duties optimally as stated in article 20 of Law of the Republic of Indonesia Number 14 of 2005 concerning Teachers and Lecturers.